Potencial alelopático de extrato etanólico de Anadenanthera macrocarpa e Astronium graveolens - Goncalves Silva, Regildo Marcio [UNESP]; Saraiva, Thiago Silvestre; Silva, Renato Boreli; Goncalves, Lucivane Aparecida; Silva, Luciana Pereira (Universidade Federal de Uberlândia (UFU), 2010)
The objective of this study was to evaluate the allelophatic potential ethanol extract of leaves of Anadenanthera macrocarpa (Benth.) Brenan (angico) and Astronium graveolens Jacq (aroeira) on the biomonitor germination of Brassica chinensis (Malaysia's cabbage) and Lactuca sativa (lettuce). For the test of allelopathy was the bioassay of germination of B. chinensis and L. sativa using solutions of ethanol extracts in different concentrations (5, 10 and 20 mg / mL) with continuous light for 11 days. The experimental and control groups were divided into the Petri dish containing 50 seeds of B. chinensis and L. sativa each. Were performed six replicates for each concentration of extract of leaves of A. macrocarpa and A. graveolens and the negative control (water). The rolling action of the treatments was performed by quantitative observation and monitoring of germination every six hours. The results show that the ethanol extract of A. macrocarpa and A. graveolens presents allelopathic potential, regardless of the concentration used, but with answers dose-dependent, and thus able to interfere directly in germination, average speed and time of germination biomonitor of B. chinensis and L. sativa.

O objetivo deste trabalho foi avaliar o potencial alelopático do extrato etanólico das folhas de Anadenanthera macrocarpa (Benth.) Brenan (angico) e Astronium graveolens Jacq (aroeira) na germinação biomonitorada de Brassica chinensis (couve-da-malásia) e Lactuca sativa (alface). Para o teste de alelopatia foi realizado o bioensaio de germinação de sementes de B. chinensis e L. sativa utilizando soluções dos extratos etanólicos em diferentes concentrações (5, 10 e 20 mg/mL) com luz contínua por 11 dias. Os grupos experimentais e controle foram separados em placa de Petri contendo 50 sementes de B. chinensis e L. sativa cada. Foi realizado seis repetições para cada concentração de extrato da folha de A. macrocarpa e A. graveolens e o controle negativo (água). O seguimento evolutivo dos tratamentos foi realizado pela observação quantitativa e monitoramento da germinação a cada seis horas. Os resultados obtidos demonstram que o extrato etanólico de A. macrocarpa e de A. graveolens apresenta potencial alelopático, independente da concentração utilizada, mas com resposta dose dependente, sendo assim capaz de interferir diretamente na germinabilidade, velocidade média e no tempo de germinação biomonitorada de B. chinensis e L. sativa.
Allelopathy potential of etanolic extract of Anadenanthera macrocarpa and Astronium graveolens
Keywords: Allelopathy; Seed germination; Angico; Aroeira